(untitled) (Indo-MathEdu Intellectuals Journal, 2023)
The learning of biology encompasses two main dimensions, namely products and processes, which ideally should not be separated. However, in practice, dominant biology learning still focuses primarily on the product dimension. One solution to address this issue is to develop guided inquiry-based biology learning modules and concept maps. This developmental research aims to produce biology learning modules that meet valid criteria. The development model used refers to the Plomp model. The instruments used include questionnaires and validation sheets. The validation results by the learning design validator were 95.67 (valid), the biology learning material validator was 91.72 (valid), and the biology subject teacher validator was 94.32 (valid). Thus, the developed guided inquiry-based biology learning module and concept map meet the valid criteria